2015
DOI: 10.1097/mjt.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Vilazodone in Hepatic Impairment

Abstract: Vilazodone, a selective serotonin reuptake inhibitor and 5-HT1A partial agonist approved for the treatment of major depressive disorder, is extensively hepatically metabolized. The pharmacokinetics, tolerability, and safety of vilazodone were investigated in 2 trials comparing participants with hepatic impairment with healthy controls. In these phase 1, open-label, parallel-group, single-dose pharmacokinetic studies, vilazodone (20 mg) was administered to participants with mild, moderate, or severe hepatic imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…As expected, impaired renal function does not affect the pharmacokinetics of vilazodone, while severe hepatic impairment led to vomiting in 4/8 patients treated with vilazodone, as opposed to 0/8 patients with severe hepatic impairment not treated with vilazodone (Boinpally et al 2013;Boinpally et al 2015). It has been reported that polymorphisms or SNP haplotypes affect the therapeutic response and the incidence of nausea and vomiting upon treatment with vilazodone (Rickels et al 2009;Lindsey 2011).…”
Section: Vilazodonesupporting
confidence: 65%
“…As expected, impaired renal function does not affect the pharmacokinetics of vilazodone, while severe hepatic impairment led to vomiting in 4/8 patients treated with vilazodone, as opposed to 0/8 patients with severe hepatic impairment not treated with vilazodone (Boinpally et al 2013;Boinpally et al 2015). It has been reported that polymorphisms or SNP haplotypes affect the therapeutic response and the incidence of nausea and vomiting upon treatment with vilazodone (Rickels et al 2009;Lindsey 2011).…”
Section: Vilazodonesupporting
confidence: 65%
“…We think it is unlikely that metabolites M10 or M13 cross-react with amphetamines immunoassays as these are very close in structure to vilazodone. However, it should be pointed out that the reported metabolic pathway for vilazodone has only been worked out in adults, with essentially no data on the metabolic pathway for vilazodone in young children [4, 1315]. A number of drug-metabolizing enzymes show significant age-dependent differences in expression and functional activity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Published pharmacokinetic studies of vilazodone in adults show maximum serum/plasma concentrations of approximately 150 ng/mL or below for vilazodone and M17 [4, 13]. A report of two children who experienced seizures following accidental vilazodone ingestion reported serum concentrations of vilazodone [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetics of vilazodone were similar in participants with mild, moderate, or severe hepatic impairment and healthy controls following a single, 20-mg oral dose of vilazodone. 11 Thus, dose adjustment is not needed for patients with major depressive disorder who have mild, moderate, or severe hepatic impairment. Likewise, another study suggested that no dose adjustment was required for patients having mild to moderate renal dysfunction.…”
Section: General Informationmentioning
confidence: 99%